Experimental study of perturbative particle transport in the HL-2A tokamak. Issue 9 (September 2020) - Zhang, B.Y.; Inagaki, S.; Shi, Z.B.; Zhong, W.L.; Zou, X.L.; Jiang, M.; Yang, Z.C.; Shi, P.W.; Chen, C.Y.; Xiao, G.L.; Feng, B.B.; Song, X.M.
Abstract: Perturbative particle transport experiment has been performed in the HL-2A tokamak by using supersonic molecular beam injection (SMBI) as an external particle source. The spatiotemporal evolution of edge density perturbation is traced and the particle source and the flux-gradient relation are obtained experimentally. The flux-gradient relation is found to be far from the diffusive model and three different transport processes are revealed, including pinch-dominant process, diffusion-pinch process and intermittent decays. Abstract : Nuclear physics, Plasma physics, Tokamak, Plasma, Particle transport, Supersonic molecular beam injection